O trágico na reescritura de Nélida Piñon em A força do destino: da ópera à tragicomédia - Ramos, Silvia do Nascimento Cardoso (2018)
This work seeks to investigate the presence of tragedy and tragicomedy theoregh intertextuality in the work A força do destino , of Nélida Piñon. This work, published in 1977, maintains intrinsic relationship with the opera of Giuseppe Verdi, staged in 1862, based on the Spanish drama, entitled Don Álvaro the La Forza del destino, from the namesake title, the characters with identical names-Álvaro, Leonora, Corral, Marquis de Calatrava and Carlos, the similarity of historical time and geographical spaces, the maintenance of sequential units and actions of the original history of the opera. The objective is to develop a critical study in which the contexts in question are demonstrated. Thus, the work wasdivided into three chapters: in the first, we analyze the tragedy in its evolutions. In this perspective, we have made a journey on the tragic: the tragic imitation of the actions in Western culture; Of the opera in its tragic aspect to the tragicomedy of contemporary narrative. In the second chapter the study was carried out in the context in which we analyzed the opera of Verdi in the strength of the destiny in its innovative process, we seek to understand in a synthesized way the opera in its historical context, and the opera and the Mímese narrative. In the third chapter, we looked at the question of Intertextuality and parody in the narrative the strength of destiny; where there was, a study focused on intertextuality, parody, polyphony and Metanarrative. To understand the tragic we did a study from Aristotle. Already to analyze the tragic in the corpus work, we walk the path from the studies in Hegel and Friedrich Nietzsche, applied theorists with regard to the relation of each one to the modern tragedy. As for tragicomedy we Plautus and Terentius, Umberto Eco, Bakthin and other scholars of this subject, woven by a significant intertextual context, parodic, polyphonic and metanarrative, we did a study based on Bakthin and other theorists who Take care of the matter. We note that Nélida Piñon, in this work (re) creates in a self-conscious way the boundaries between the real and the fictional, making the whole process visible to the reader. From these theories between tragedy, tragicomedy and intertextuality, we observe a singular construct that intensifies and transgresses into a contemporary work.